An Overview of the Journey of Political Parties in Indonesia from a Socio-historical Perspective - Safrizal Rambe; Zulkarnain (Polit Journal Scientific Journal of Politics, 2022)
Democratic country usually generates a healthy, growing, and rooted political party. In Indonesia, political parties had long been known before Indonesia's independence. At that time, the political party became the medium of the founding fathers' struggle to fight against colonialism. Since Indonesia's Independence Day, the existence of a political party was admitted and supported by the government. This study needs to make a political point of view. It will enrich learning and understanding of the existence of political parties concerning the development of Political Science in Indonesia. The focus of this study is to describe how the political party's history and its role from Orde Lama until the Orde Baru era in Indonesia. This study uses a qualitative research method, and data interpretation will be analyzed with the descriptive analysis method. In the meantime, data validation will be checked and rechecked after collecting data. This study concludes that Indonesian politics has experienced a significant shift in values and practices. Indonesia started the state process with the concept of gotong royong. It was oriented to the welfare of the people with the leadership of the assembly institution as the people's representative in the form of deliberation.